2008
DOI: 10.1002/fuce.200800011
|View full text |Cite
|
Sign up to set email alerts
|

Partially Fluorinated Arylene Polyethers and Their Ternary Blend Membranes with PBI and H3PO4. Part I. Synthesis and Characterisation of Polymers and Binary Blend Membranes

Abstract: A partially fluorinated polyether ionomer from polycondensation of decafluorobiphenyl with 2,2‐bis(4‐hydroxyphenyl)hexafluoropropane, followed by sulphonation with H2SO4 (60% SO3), has been prepared and optimised in terms of molecular weight and sulphonation degree. The partially fluorinated ionomer has been blended with poly(2,2′‐m‐phenylene‐5,5′‐bibenzimidazole) (PBI), yielding base–acid blends with PBI in excess. The base–acid blend membranes have been characterised in terms of solubility in DMAc, water upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 46 publications
3
45
0
Order By: Relevance
“…Similarly, Lobato et al [29] examined FTIR spectra of high molecular weight PBI membranes before and after the treatment in Fenton solutions, however, without finding significant changes in the spectra between 2,000 and 4,000 cm -1 associated with the N-H stretching modes and between 1,000 and 1,700 cm -1 associated with benzimidazole rings. On the other hand, significant weight losses have been reported for membranes after the Fenton test in 3% H 2 O 2 containing 4 ppm Fe 2+ at 68°C [30,31], ranging from 10% to 40% depending on the initial molecular weight of the polymer. Under even harsher conditions, i.e.…”
Section: Oh Ormentioning
confidence: 96%
“…Similarly, Lobato et al [29] examined FTIR spectra of high molecular weight PBI membranes before and after the treatment in Fenton solutions, however, without finding significant changes in the spectra between 2,000 and 4,000 cm -1 associated with the N-H stretching modes and between 1,000 and 1,700 cm -1 associated with benzimidazole rings. On the other hand, significant weight losses have been reported for membranes after the Fenton test in 3% H 2 O 2 containing 4 ppm Fe 2+ at 68°C [30,31], ranging from 10% to 40% depending on the initial molecular weight of the polymer. Under even harsher conditions, i.e.…”
Section: Oh Ormentioning
confidence: 96%
“…It has however been found that the loss of low molecular fractions (oligomers) of the sulfonated polymer (SFS001) does occur [19,20,32], which can account for the slight weight decrease noted after treatment. While the change in thickness, indicative of the one dimensional changes (Section Weight and thickness change in Experimental) measured for membrane 03-CEM, as indicated in Table 3, is still acceptable at 80 C, the thickness change at 95 C is too high for the application in an electrolyser.…”
Section: Weight and Thickness Changementioning
confidence: 97%
“…In addition to evaluating the novel cross-linking concept of the acid-base PBI-containing blend membranes, the influence of partially fluorinated blend components on the stability of the blend membranes within an H 2 SO 4 environment will be investigated. It has been reported in previous studies that partially fluorinated polymers have in some cases shown high proton-conductivities and durability's [29,30] due to the apparent difference in bond strength energies present between the respective CeF and CeH bonds [26,31,32]. However, for SO 2 application still has to be determined whether the best membrane properties are obtained when only partially fluorinated and non-fluorinated polymer components are blended with each other, or when non-fluorinated and partially fluorinated polymers are combined.…”
Section: Electrolysismentioning
confidence: 98%
“…Zhang and Mukerjee [65] reported a weight loss of 11% for SPES-40 (SD = 80 mol.%) after 30 min in the Fenton's reagent at 68°C, while after 1 h the polymer broke down completely into dark, powder-like pieces. For comparison, Kerres et al [66] reported that Nafion 117 lost only 1% after 20 h exposure in the same Fenton solution at 68°C, but Miyatake et al [7] found a weight loss of 2% after immersion in 3 wt.% H 2 O 2 containing 2 ppm FeSO 4 at 80°C for 1 h. Moreover, another thoroughly studied high temperature polymer electrolyte, PBI, has been reported to break into small pieces after about 30 min exposure to the Fenton solution at 68°C [66]. In order to further investigate the effect of the peroxy radicals on the sulfonated copolymers, samples were tested by means of DMA after treatment with the Fenton solution.…”
Section: Oxidative Stabilitymentioning
confidence: 98%